2013
DOI: 10.11607/jomi.3025
|View full text |Cite
|
Sign up to set email alerts
|

Split-Mouth Comparison of the Accuracy of Computer-Generated and Conventional Surgical Guides

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
159
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(171 citation statements)
references
References 0 publications
6
159
1
5
Order By: Relevance
“…Similarly, extraoral implant placement accuracy was 1.5 mm [139]. Farley reported that some stereolithography templates required intraoral relining to improve the fit on the adjacent teeth [28]; however, this discrepancy could not be related to manufacturing process. Instead, clinical variability such as soft tissue fit and compressibility and implant insertion in less dense bone may be the main source of the discrepancies [27, 139].…”
Section: Computer-aided Production Streamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, extraoral implant placement accuracy was 1.5 mm [139]. Farley reported that some stereolithography templates required intraoral relining to improve the fit on the adjacent teeth [28]; however, this discrepancy could not be related to manufacturing process. Instead, clinical variability such as soft tissue fit and compressibility and implant insertion in less dense bone may be the main source of the discrepancies [27, 139].…”
Section: Computer-aided Production Streamsmentioning
confidence: 99%
“…Overall, the accuracy of the surgical guides could be improved by fabricating them to fit the alveolar bone instead of soft tissue and by the use of fixation screws [27, 29]. Nevertheless, a split mouth clinical study revealed that the stereolithography guides allowed for implant placement closer to the planned position than conventionally fabricated guides [28]. …”
Section: Computer-aided Production Streamsmentioning
confidence: 99%
“…() described a specific drill design avoiding the use of drill keys or drills with different sheath diameters. Recent publications (Farley et al. ; Vercruyssen et al. ) have shown that the most significant error with guided surgery is made in vertical direction (depth).…”
Section: Executionmentioning
confidence: 99%
“…• Recent publications (Farley et al 2013;Vercruyssen et al 2014a) have shown that the most significant error with guided surgery is made in vertical direction (depth). Horizontal inaccuracies are clearly less.…”
Section: Some Precautionsmentioning
confidence: 99%
“…Fully restrictive guided surgery requires less skill than does freehand surgery and may improve the result. [14][15][16] A fully restrictive guide can be fabricated with one of 2 paths. The digital path uses cone-beam computed tomography (CBCT), dedicated software, and computeraided design/computer-aided manufacturing (CAD/ CAM) technologies.…”
mentioning
confidence: 99%